The patent-license system of Ukraine in the second half of the XX century - Tverytnykova, E. E.; Gutnyk, M. (Дніпровський національний університет імені Олеся Гончара, 2020)
The formation of the patent-licensing system of Ukraine during the second half of the XX century is investigated. It is established that the first funds of technical literature, which was necessary for patent work, were created in the departments of the institutes of the Academy of Sciences of the USSR in the first postwar years. For example, the fund of scientific and technical literature, documentation, patents and inventions began to form in the Institute of Electrical Engineering of the USSR. It was established in 1944. But various special centers for providing information support for the development of the patent and license business were organized a somewhat later. In particular, at the Institute of Electrical Engineering of the Academy of Sciences of the USSR only 20 years later in 1964. Employees were making a preliminary examination of applications for inventions and expanding the funds of scientific and technical documentation, were completing foreign patent documentation from foreign countries. A network of special Patent Departments was created on the basis of the higher technical institutions. A small group for the systematization of patent information was created at the Kharkiv Polytechnic Institute in 1967. In 1971, the patent office was also established at the Odessa Polytechnic Institute. In 1974, at the Kyiv Polytechnic Institute an organizational and analytical department was created, it contributed to the development of inventive activities of the Institute. The intensification of inventive search occurred in the 1980s and was aimed at improving quality, which contributed to the creation of prospective, competitive world-class developments and their introduction into industry. During this period, the vast majority of scientists took part in patent and licensing activities, a large number of patents were obtained and scientific and technical cooperation was started on a commercial basis with the conclusion of licensing agreements. A number of devices were patented in the following countries: Spain, Italy, England, Switzerland, Japan, Germany, Hungary, Poland, Bulgaria and others. In the early 1990s, the situation with inventive and patent licensing activities changed. A significant reduction in the number of inventions demonstrated the general state of scientific research in the country.

Досліджено становлення патентно-ліцензійної системи України впродовж другої половини ХХ ст. Встановлено, що перші фонди технічної літератури, яка була необхідна для патентної роботи, створювалися у відділах інститутів АН УРСР у перші повоєнні роки. Наприклад, фонд науково-технічної літератури, документації, патентів та винаходів розпочав формуватися в Інституті електротехніки УРСР, його створено 1944 р. Але різні спеціальні осередки для надання інформаційної підтримки для розгортання патентноліцензійної справи були організовані декілька пізніше. Зокрема в Інституті електротехніки АН УРСР – лише через 20 років, у 1964 р. Співробітники проводили попередню експертизу заявок на винаходи, розширяли фонди науково-технічної документації, здійснювали комплектацію закордонної патентної документації. Мережа спеціальних патентних відділів була створена і на базі вищої технічної школи. Невелика група з систематизації патентної інформації була створена в Харківському політехнічному інституті в 1967 р. У 1971 р. патентне бюро було створено також в Одеському політехнічному інституті. У 1974 р. в Київському політехнічному інституті створили організаційно-аналітичний відділ, що сприяло розвитку винахідницької діяльності інституту. Активізація винахідницького пошуку припадала на 1980-ті рр. і була спрямована на підвищення якості, що сприяло створенню перспективних, конкурентоспроможних розробок світового рівня та впровадженню їх у промисловість. На початку 1990-х рр. ситуація з винахідницькою та патентно-ліцензійною діяльністю змінилася. Значне скорочення кількості винаходів демонструвало загальний стан наукових досліджень у країні.
Патентно-ліцензійна система України у другій половині ХХ ст.
Keywords: invention; patent; copyright certificate; licensing; technical sciences; research institutions; Ukraine; винахідництво; патент; авторське свідоцтво; ліцензування; технічні науки; науково-дослідні установи; Україна